Enhanced 'In-situ' catalysis via microwave selective heating: catalytic chain transfer polymerisation - Adlington, Kevin; McSweeney, Robert; Dimitrakis, Georgios; Kingman, Samuel W.; Robinson, John P.; Irvine, Derek J. (Royal Society of Chemistry, 2014)
An extremely facile, single stage, ‘in-situ’, Catalytic Chain Transfer Polymerisation (CCTP) process has been identified, where the optimal polymerisation process was shown to depend upon a combination of catalyst characteristics (i.e. solubility, sensitivity, activity) and the method of heating applied. In comparison to the current benchmark catalyst, the preparation of which is only about 40 % efficient, this represents a significant increase in waste prevention/atom efficiency and removes the need for organic solvent. It was also shown possible to significantly reduce the overall ‘in-situ’ reaction cycle time by adopting different processing strategies in order to minimise energy use. The application of microwave heating was demonstrated to overcome system diffusion/dilution issues and result in rapid, ‘in-situ’ catalyst formation. This allowed processing times to be minimised by enabling a critical concentration of the species susceptible to microwave selective heating to dominate the heat and mass transfer involved.